Gender equality with difference : a yijing yin-yang approach - Zhang, Lili (Nanyang Technological University, 2019)
In this dissertation, I argue that gender equality should be premised on gender difference in the Yijing yin-yang thinking paradigm. To support the thesis, I begin with a brief review of three representative sexist theories in mainstream feminism: (1) women are conceptual others, inferior to men; (2) women are “mutilated males,” possessing a degraded position; and (3) women’s experience is replaced by men’s. I argue that these sexist norms are part of “the one-sex model,” which is largely dominated by the exclusive dualistic thinking paradigm and its hierarchical evaluating system. Worse, this paradigm causes a dilemma of gender equality. This dilemma is the incompatibility between equality in sameness and equality in difference.